FORMULATION AND OPTIMIZING OF A SKIN BARRIER REGENERATING COSMECEUTICAL PRODUCT - JUNCAN, A. M. (Studia Universitatis Babeș-Bolyai Physica, 2015)
This study has as main objective the development and formulation of a skin barrier regenerating dermatocosmetic product for daily care, which incorporates effective emollients, such as Shea butter, an emollient and moisturizing cosmetic ingredient recognized for its regenerative effects, and an innovative emollient - Sucragel AOF (Glycerin (and) Prunus Amygdalus Dulcis (Sweet Almond) Oil (and) Sucrose LAURATE (and) Citrus Aurantium Dulcis (Orange) with moisturizing proven cosmetic eficacy and GATULINE® BIO SKIN-REPAIR (Alcohol (and ) Water (and) onopordum Acanthium Flower/Leaf/Stem Extract), used in the developed formulation to support the cosmetic claimed of the product. An important study is the quality control of the regenerating cream by determining the physico-chemical characteristics and appropriate pharmacotechnical (pH, viscosity) characteristics, both initially and over time (30 days from the preparation of the product). The formulation is monitored under accelerated stability studies over a period of 30 days while maintaining the product at 4, 20 and 40 °C.